Risk aversion and the teaching profession: An analysis including different forms of risk aversion, different control groups, selection and socialization effects - Adam Ayaita; Kathleen Stürmer (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
Risk aversion might affect current and potential teachers' reaction to reforms, in particular payment reforms. However, evidence on teachers' risk aversion in comparison to other occupations is limited. The present study is based on twelve waves of a representative German data set (N = 18,381) and shows that teaching relates positively to risk aversion, especially to risk aversion with respect to occupational career. Teachers score higher in risk aversion even than other civil servants. Risk-averse individuals are attracted to teaching from career outset; moreover, our results suggest an additional socialization effect during the employment that may reinforce this relationship.
Keywords: H75; I28; J20; J45; M50; O30; 330; teachers; teaching; motives; risk aversion